Influenza vaccination and humoral alloimmunity in solid organ transplant recipients. (17th June 2014) - Vermeiren, Pieter; Aubert, Vincent; Sugamele, Rocco; Aubert, John‐David; Venetz, Jean‐Pierre; Meylan, Pascal; Pascual, Manuel; Manuel, Oriol
Summary Annual influenza vaccination is recommended in solid organ transplant (SOT) recipients. However, concerns have been raised about the impact of vaccination on antigraft alloimmunity. We evaluated the humoral alloimmune responses to influenza vaccination in a cohort of SOT recipients between October 2008 and December 2011. Anti‐HLA antibodies were measured before and 4–8 weeks after influenza vaccination using a solid‐phase assay. Overall, 169 SOT recipients were included (kidney = 136, lung = 26, liver = 3, and combined = 4). Five (2.9%) of 169 patients developed de novo anti‐HLA antibodies after vaccination, including one patient who developed donor‐specific antibodies (DSA) 8 months after vaccination. In patients with pre‐existing anti‐HLA antibodies, median MFI was not significantly different before and after vaccination (P = 0.73 for class I and P = 0.20 for class II anti‐HLA antibodies) and no development of de novo DSA was observed. Five episodes of rejection (2.9%) were observed within 12 months after vaccination, and only one patient had de novo anti‐HLA antibodies. The incidence of development of anti‐HLA antibodies after influenza vaccination in our cohort of SOT recipients was very low. Our findings indicate that influenza vaccination is safe and does not trigger humoral alloimmune responses in SOT recipients.